Revision of the genus Ferkeria Roewer, 1947, with the description of a new species (Opiliones: Laniatores: Cosmetidae) - Monteiro, Yago Ferro; Pinto-Da-Rocha, Ricardo (Zootaxa, 2015)
A new diagnosis for the cosmetid genus Ferkeria Roewer, 1947 is proposed. The type species, F. vestita Roewer, 1947 is redescribed and a new species, Ferkeria flavicoxae sp. nov., is described from Zongo, La Paz, Bolivia. The new species differs from the only other species of the genus by: yellow-white colored coxa IV (orange-brown in F. vestita); armature of scutal areas I–III with rounded tubercles (spiniform in F. vestita) and conspicuous tarsal process (reduced in F. vestita).